Some types of fuzzy open sets in fuzzy topological groups - Hmod, Mohamad Thigeel; A. Al-khafaji, Munir; Majeed, Taghreed Hur (International Journal of Advanced Mathematical Sciences, 2015)
The aim of this work is to introduce the definitions and study the concepts of fuzzy open (resp, fuzzy Î±- open, fuzzy semi- open, fuzzy pre- open, fuzzy regular- open, fuzzy b- open, fuzzy Î²- open) sets in fuzzy topological groups, and devote to study and discuss some of the basic concepts of some types of fuzzy continuous, fuzzy connected and fuzzy compact spaces in fuzzy topological groups with some theorems and Proposition are proved.